2018
DOI: 10.14356/kona.2018012
|View full text |Cite
|
Sign up to set email alerts
|

Size Control of Polymeric Particle in Soap-Free Emulsion Polymerization

Abstract: The process of synthesis of polymeric particle in soap-free system was observed in-situ on the molecular scale by using an atomic force microscope (AFM). Using cationic water-soluble initiators enabled all of the polymeric materials to be adsorbed on the mica surface electrostatically. This adsorption technique of polymeric materials in the bulk obtained the AFM images of them throughout the reaction and to discuss the real growth mechanism of polymeric particles. The followings are found; the polymeric materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…It is also important to mention that no relation was found between the reaction variables used in this study. Yamamoto and Higashitani [ 30 ] have suggested that a positive potential for the PMMA microspheres is associated to the functional groups in the initiator V50. If this were the case, the bands corresponding to C-N and N-H vibrations would be present in the FT-IR and Raman spectra.…”
Section: Resultsmentioning
confidence: 99%
“…It is also important to mention that no relation was found between the reaction variables used in this study. Yamamoto and Higashitani [ 30 ] have suggested that a positive potential for the PMMA microspheres is associated to the functional groups in the initiator V50. If this were the case, the bands corresponding to C-N and N-H vibrations would be present in the FT-IR and Raman spectra.…”
Section: Resultsmentioning
confidence: 99%
“…As an environmentally-protective measure, the synthesis should be carried out in water and this was only partially possible. Acrylic acid was added as the comonomer during the emulsion polymerization of N-isopropylacrylamide (NIPA) and N,N-diethylacrylamide (DEA) [32][33][34][35][36][37]. Unfortunately, the molar content of AA in these gels did not exceed 40%.…”
Section: Introductionmentioning
confidence: 99%